Hubungan praktik pemberian MP-ASI dan malnutrisi (6-23 bulan) di negara berkembang: Scoping Review berbasis indikator WHO - Kemuning, Bethrix Angelita Sukma; Raflihudin, Mohammad Zen; Winarni, Sri (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Complementary feeding plays a crucial role in preventing malnutrition during early childhood. However, inappropriate complementary feeding practices that do not align with the World Health Organization (WHO) Infant and Young Child Feeding (IYCF) guidelines remain prevalent in developing countries, contributing to high rates of undernutrition and child mortality worldwide.Objective: This review aimed to map the current scientific evidence on the association between complementary feeding and malnutrition among children aged 6–23 months in developing countries, based on the latest WHO IYCF indicators.Methods: This scoping review followed the PRISMA-ScR framework. Literature searches were conducted across Scopus, PubMed, Cochrane Library, and Web of Science databases for English and Indonesian publications from 2020–2025. Eligible studies included observational research examining the relationship between WHO IYCF indicators and child nutritional outcomes. Study quality was assessed using The Joanna Briggs Institute (JBI) Critical Appraisal Tools, and data were analyzed descriptively without quantitative synthesis.Results: Of 4,454 screened articles, 10 met the inclusion criteria. The mapped evidence consistently showed that inappropriate complementary feeding practices are associated with stunting, wasting, and underweight among children. However, the strength of associations varied due to contextual differences in socioeconomic conditions, dietary culture, national nutrition programs, and variations in the application and measurement of WHO indicators.Conclusion: Appropriate complementary feeding practices based on WHO IYCF indicators are positively linked to better nutritional outcomes in children aged 6–23 months. Strengthening evidence-based, multisectoral interventions and longitudinal research is essential to address disparities in child nutrition.